Chinese university students' beliefs about second language acquisition - Fu, Xitian (2015)
Xitian, Fu. 2015. Beliefs about Second Language Acquisition from Chinese University Students. Master's Thesis in Education. University of Jyväskylä. Department of Education. Beliefs about second language acquisition (SLA) have intrigued pioneer investigators for more than 30 years. However, until quite recently, most studies have been conduced in the Western school context. This study aims to investigate Chinese university students’ beliefs about second language acquisition (SLA) originating from a completely different social context. This study attempts to obtain new insights of English language learning as experienced by Chinese university students within a specific social cultural context.